Pendopo Sebagai Ruang Multiplicity Dalam Narasi Branding Kota Banyuwangi yang Inklusif - Azizah, Alya Lailatul; Kusdiwanggo, Susilo; Titisari, Ema Yunita (Hasta Wiyata, 2025)
Pendopo Sabha Swagata Blambangan in Banyuwangi is an architectural space containing overlapping social, political, and cultural roles. These layers of meaning relate to Deleuze and Guattari’s concept of multiplicity, where the pendopo functions not only as the regent’s official residence but also as a public space, tourist destination, and medium for articulating the city’s identity. This study seeks to answer “how is multiplicity in the pendopo used in Banyuwangi’s city branding strategy in the context of culture and urban identity?”. This research applies a qualitative approach using inductive coding. Data were collected through in-depth interviews and field documentation, then analyzed using the theoretical framework of multiplicity. The findings show that the pendopo serves as an arena of becoming, containing layered meanings and multiple functions. It is not reduced to a single symbol but emerges as a network of political space, cultural-historical narratives, and an active public realm. Banyuwangi’s branding strategy through the pendopo is built not on fixed visual representation, but through the involvement of space that is inclusive and relational. In this context, multiplicity becomes a key framework for understanding how urban space is dynamically constructed as part of cultural practice and open identity representation.